Low-carbon low-sulfur low-cost alkaline particle covering agent and production method thereof
By using low-carbon and low-sulfur alkaline particle covering agent, the existing ladle covering agent has solved the problems of poor insulation effect, pollution and high cost during the smelting process. The homogenization process and solid waste materials are used to achieve environmental protection and low Cost molten steel purification and insulation effect, suitable for a variety of steel types.
Patent Information
- Application Number
- CN202411432864.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-10-15
AI Technical Summary
The existing ladle cover agent has problems such as poor insulation effect, polluting the molten steel, causing flue gas pollution, high cost and unfriendly environment during the smelting process. In particular, the carbonized rice husk cover agent produces a large amount of flue gas pollution and density during the smelting process. Small causes dust and cannot effectively purify the molten steel.
Low-carbon and low-sulfur alkaline particle covering agent is used to replace refractory materials by solid waste materials, homogenized binder-free cold forming preparation process, and 50-70% activated carbon fly ash or slag and 20-40% lime dust removal Ash, 6-8% dolomite dust removal ash, 2-4% activated carbon dust removal ash, combined with methyl silicone oil fluidization treatment, an alkaline particle covering agent with particle size of 0.5-2mm is prepared to reduce costs and improve spreadability and insulation effect .
It has achieved a low-cost and environmentally friendly alkaline particle covering agent, with good thermal insulation, spreadability and purification effects, and will not cause carbon and sulfur increase in molten steel, and is environmentally friendly. It is suitable for special steels such as silicon steel and stainless steel.
Smart Images

Figure CN119263853A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metallurgical auxiliary materials, and in particular to a low-carbon, low-sulfur, and low-cost alkaline particle covering agent and a production method thereof. Background Art
[0002] Ladle covering agent is a kind of artificial auxiliary material added into the ladle to cover the surface of molten steel during the smelting process. It has the following functions: Insulation and heat preservation, preventing crusting on the surface of molten steel. The covering agent has a significant insulation and heat preservation effect. The covering agent covers the surface of molten steel to prevent the molten steel from being exposed to the air, causing the temperature of the molten steel to drop rapidly, thus causing crusting on the surface of the liquid and freezing of the nozzle.
[0003] Isolate the air and prevent secondary oxidation of molten steel. After the covering agent is added, a liquid slag layer with poor air permeability is formed, which isolates the molten steel from the air, prevents the secondary oxidation of the molten steel, and reduces the inclusions in the molten steel.
[0004] Absorb non-metallic inclusions on the surface of molten steel and purify molten steel. The covering agent forms a slag layer of a certain thickness on the surface of molten steel, which can absorb non-metallic inclusions, refractory particles and other floating objects floating on the surface of molten steel, thus playing a role in purifying molten steel.
[0005] At present, most steel mills and most steel grades use ordinary ladle covering agents, which are acidic and mainly composed of SiO2, Al2O3, CaO, MgO, and C, among which w(SiO2)>40%, w(C)=15-40%, and w(CaO) / w(SiO2)<0.5. The biggest advantage of acidic covering agents is good thermal insulation effect, and the biggest disadvantage is that they cannot purify molten steel and may even pollute molten steel. Therefore, alkaline covering agents that can purify molten steel were developed, but the biggest disadvantage of alkaline covering agents is poor thermal insulation, and their thermal conductivity is twice that of acidic covering agents.
[0006] At present, most steel mills use carbonized rice husk as the main raw material for covering agents. The defects of using carbonized rice husk for thermal insulation are: a large amount of flue gas is generated during the production process of carbonized rice husk, which pollutes the air; carbonized rice husk has a high melting point and is not easy to melt on the surface of molten steel, and cannot form a liquid slag layer, has poor spreadability, and has poor thermal insulation effect, and does not have the metallurgical function of absorbing floating inclusions in molten steel; when using carbonized rice husk, its density is small, and a large amount of dust is generated during the addition process and the slag pouring process, which is not friendly to the environment and has a relatively high overall price.
[0007] In addition, the carbon content in steel is one of the elements that must be controlled in the production process of pure steel. The covering agents used by domestic steel companies generally contain a large amount of carbonaceous materials, which will increase the carbon content in the molten steel. To effectively prevent the carbon increase of molten steel in the ladle, it is best to use a carbon-free or low-carbon ladle covering agent, which requires the content of carbonaceous materials in the ladle covering agent to be as low as possible.
[0008] The purpose of the present invention is to provide a low-carbon, low-sulfur, low-cost, environmentally friendly alkaline particle covering agent and a production method thereof. The product can reduce the heat loss of molten steel and purify the molten steel without causing carbon and sulfur increase in the molten steel and is environmentally friendly.
[0009] The purpose of the present invention is achieved in this way: on the one hand, solid waste materials are used to replace refractory materials, thereby greatly reducing the cost of raw materials; on the other hand, the main raw materials do not need to use a grinding process, and the finished product preparation adopts a homogenized binder-free cold forming preparation process (homogenization treatment, dry extrusion strip making, crushing and whole granulation composite process) to replace wet spray granulation or semi-dry extrusion granulation, thereby further reducing costs. Summary of the invention
[0010] The purpose of the present invention is to provide a low-carbon, low-sulfur, low-cost alkaline particle covering agent and a production method thereof in view of the above problems.
[0011] The object of the present invention is achieved in this way: a low-carbon, low-sulfur, low-cost alkaline particle covering agent, characterized in that: the ingredients and mass percentages are as follows: CaO: 28-42%, MgO: 3-5%, Al2O3: 12-20%, Fe2O3: 1-3%, SiO2: 25-36%, S: 0.01-0.04%, C <5%, H20: <1%, methyl silicone oil 0.2%-0.3%, and the rest are impurities that do not affect the use effect; hemisphere point 1500-1750℃, R (alkalinity) 1.0-1.5, melting speed 60-120 seconds, bulk density 0.6-0.9, and particle size 0.5-2mm.
[0012] The raw materials of alkaline granular covering agent are 50-70% activated carbon fly ash or slag, 20-40% lime dust ash, 6-8% dolomite dust ash, and 2-4% activated carbon dust ash.
[0013] A method for producing a low-carbon, low-sulfur, and low-cost alkaline granular covering agent, comprising the following steps: Step 1: pump lime dust removal ash, dolomite dust removal ash, and activated carbon dust removal ash into a raw material bin for standby use by a tank truck; Step 2: After activated carbon fly ash or slag is separated by a closed drum screen, fine powder <0.1 mm is sent to the raw material bin by a bucket elevator for standby use; Step 3: Various raw materials are mixed according to 50-70% activated carbon fly ash or slag, 20-40% lime dust removal ash, 6-8% dolomite dust removal ash, and 10-20% lime dust removal ash. The proportion of stone dust removal ash and 2-4% activated carbon dust removal ash is weighed by a metering dragon, sent to a stirrer for uniform mixing, and then sent to the intermediate warehouse for standby through a bucket elevator; Step 4: The mixed material in the intermediate warehouse falls to a forced screw feeder with a compression ratio of 5:1 through a metering feeder with a locked air valve. The pressure of the forced screw feeder is 10-12.5Mpa; Step 5: The raw materials after the feeder are squeezed into a high-pressure strip roller press. Under the pressure of 20-25Mpa, the extruded blocks are formed into oval long strips with a length of 100±50mm, a width of 10±5mm, and a thickness of 8±4mm; Step 6: After the oval long strips leave the roller area, they are automatically demolded and fall into a blade crusher for crushing; Step 7: The strips and fragments after being crushed by the blade crusher fall into a cage granulator. Under the action of the granulator with a filter screen of 2mm, the strips and fragments are granulated into 0-2mm particles and naturally fall into a multi-layer vibrating screen; Step 8: After being separated into 0. The qualified particle size of 5-2mm, and the materials of >2mm and <0.5mm are returned to the intermediate bin through the bucket elevator to participate in the next round of briquetting; Step 9: The finished products of qualified particle size are fluidized and stirred in the passivation chamber at 80-130℃ with 0.2%-0.3% atomized methyl silicone oil to obtain a low-carbon and low-sulfur alkaline particle covering agent. The methyl silicone oil is heated to 100-130℃ by a heater and atomized through a disc fine-pore nozzle under the action of a 0.5-0.6Mpa booster pump.
[0014] The beneficial effects of the present invention are as follows: the present invention provides a low-carbon, low-sulfur, low-cost, environmentally friendly alkaline granule covering agent and a production method thereof, which has the advantages of good heat preservation, uniform spreadability, no pollution such as C and S in molten steel, strong adsorption capacity for inclusions, and no final liquid slag sticking to the bag, and has the advantages of convenient operation and low cost per ton of steel, etc. It is suitable for special steels such as silicon steel, stainless steel, and ultra-low carbon.
[0015] The product of the present invention forms three layers when put into molten steel. The functional structure of the material layer is clear and the corresponding functional role is achieved. The first layer is the contact surface with the molten steel and is in a molten state, which completely isolates the possibility of the molten steel being secondary oxidized; the second layer is a transition layer, which plays a role of heat preservation; the third layer is a sintering layer, which forms a porous covering structure and plays a major role of heat preservation. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] The present invention will be further described below in conjunction with the accompanying drawings.
[0017] Figure 1 It is the flow chart of the present invention. Note: The metering dragon is also called the metering screw feeder. DETAILED DESCRIPTION
[0018] The present invention provides a low-carbon, low-sulfur, low-cost, environmentally friendly alkaline granular covering agent, whose components and mass percentages are as follows: CaO: 30-35%, MgO: 3-5%, Al2O3: 12-20%, Fe2O3: 1-3%, SiO2: 30-35%, S: 0.02-0.04%, C <5%, H20: <1%; its melting point is ≥1500°C, R (alkalinity) >1.0, melting speed is ≥60 seconds, bulk density is 0.6-0.9, and particle size is 0.5-2mm.
[0019] The low-carbon, low-sulfur, low-cost and environmentally friendly alkaline granular covering agent uses 50-70% activated carbon fly ash (or slag), 20-40% lime dust ash, 6-8% dolomite dust ash, 2-4% activated carbon dust ash and other industrial solid wastes as the main raw materials. Compared with the use of refractory raw materials, it greatly reduces the cost of raw materials.
[0020] A new type of granular coating production method, the main raw material does not need to use the grinding process, the finished product preparation adopts a homogenized binder-free cold forming preparation process (homogenization treatment, dry extrusion film strip, crushing and whole granulation composite process) to replace wet spray granulation or semi-dry extrusion granulation, further reducing costs. The preparation steps are as follows: (1) Lime dust ash, dolomite dust ash, and activated carbon dust ash are pumped into the raw material warehouse by a tank truck for standby. (2) After the activated carbon fly ash (or slag) is separated by a closed drum screen, the fine powder <0.1mm is sent to the raw material warehouse by a bucket elevator for standby. (3) Various raw materials are designed according to the formula, weighed by a metering dragon, sent to a stirrer for uniform mixing, and then sent to the intermediate warehouse by a bucket elevator for standby. (4) The mixed material in the intermediate warehouse falls to a 5:1 forced feeder through a metering feeder with a locked air valve. (5) After the feeder is used, the raw materials are squeezed into the high-pressure roller press, and under the pressure of 25Mpa, they are squeezed into 8×10×100mm oval strips. (6) The 8×10×100mm oval strips are out of the roller area, the pressure is released, the centrifugal force is not on the center line of the material, and they are automatically demolded and fall into the blade crusher for crushing. (7) After being crushed by the crusher, the material naturally falls into the cage granulator, and under the action of the 2mm filter, the material falls into the multi-layer vibrating screen. (8) After multiple vibrating screen separations, the qualified particle size of 0.5-2mm; the materials >2mm and <0.5mm are returned to the intermediate bin through the bucket elevator to participate in the next round of briquetting. (9) The qualified particle size products are treated in the passivation chamber with 0.2%-0.3% atomized methyl silicone oil fluidization, which greatly improves the fluidity and spreadability of the material.
[0021] 1. In view of the problem of low density and large amount of dust in carbonized rice husk, the present invention intends to use mineral activated carbon fly ash as the main raw material to solve the problem. Its main components are as shown in the following table.
[0022]
[0023] Note: Mineral activated carbon fly ash comes from the fly ash after the byproducts of crushing and screening of activated carbon processing enterprises and dust ash are burned and decarbonized at high temperatures in boilers in winter. Mineral activated carbon screen residue and dust ash have low calorific value, limited uses, and low prices, so they are generally sold as fuel coal.
[0024] 2. Aiming at the goal that the product of the present invention requires both high alkalinity and low carbon content and good thermal insulation effect, the raw materials of the present invention mainly use 20%-40% lime dust ash and 50%-70% activated carbon fly ash (or slag). The use of lime can ensure the high alkalinity of the covering agent, which is conducive to purifying molten steel; mineral activated carbon fly ash contains very little carbon, which can ensure that it will not cause carbon increase in molten steel; the reduction in carbon content does not affect the thermal insulation effect of the covering agent, which is determined by the highly advantageous porous and honeycomb microstructure of activated carbon fly ash, and the density is smaller than that of molten steel, and the melting point is high, so it is not easy to melt, and it plays the role of a skeleton, so that the thermal insulation layer can maintain a foamy and loose state without obvious collapse. The main components of lime dust ash are shown in the following table.
[0025]
[0026] 3. In order to improve fluidity and spreadability, a small amount of dolomite crushing dust is planned to be added, and the expansion capacity of dolomite dust removal ash due to thermal decomposition is utilized to make the covering agent spread quickly after being put into the ladle, effectively covering the surface of the molten steel and avoiding red leakage. Its main components are shown in the following table.
[0027]
[0028] Note: Dolomite mine dust: The fine dust collected from the environmental dust collector during the mining and crushing process of dolomite mines.
[0029] 4. In order to compensate for the heat loss of molten steel, it is planned to add a small amount of activated carbon dust removal ash to the raw materials, but the finished product w(C) is controlled to be less than 5%. Its main components are shown in the following table.
[0030]
[0031] 5. In order to ensure the homogeneity of the materials, all raw materials are carefully measured according to the ratio, sent into the blender and stirred evenly for use.
[0032] 6. In order to reduce the serious dust during use and cause environmental pollution, the raw materials need to be granulated.
[0033] 7. In order to reduce energy consumption and manufacturing costs, it is planned to adopt a homogenized binder-free cold forming preparation process (homogenization treatment, dry extrusion strip making, crushing and granulation composite process) to replace wet spray granulation and semi-dry extrusion granulation.
[0034] 8. In order to improve fluidity and spreadability, methyl silicone oil is used for fluidization (passivation) treatment. The functions of methyl silicone oil are: (1) moisture-proof, preventing the particles from absorbing moisture and powdering. (2) When the covering agent is added to the molten steel, it reduces the friction of the particles and plays a role in rapid spreading (fluidization). Benchmark Example
[0035] A method for producing a low-carbon, low-sulfur, and low-cost alkaline granular covering agent, comprising the following steps: Step 1: pump lime dust removal ash, dolomite dust removal ash, and activated carbon dust removal ash into a raw material bin for standby use by a tank truck; Step 2: After activated carbon fly ash or slag is separated by a closed drum screen, fine powder <0.1 mm is sent to the raw material bin by a bucket elevator for standby use; Step 3: Various raw materials are mixed according to 50-70% activated carbon fly ash or slag, 20-40% lime dust removal ash, 6-8% dolomite dust removal ash, and 10-20% lime dust removal ash. The proportion of stone dust removal ash and 2-4% activated carbon dust removal ash is weighed by a metering dragon, sent to a stirrer for uniform mixing, and then sent to the intermediate warehouse for standby through a bucket elevator; Step 4: The mixed material in the intermediate warehouse falls to a forced screw feeder with a compression ratio of 5:1 through a metering feeder with a locked air valve. The pressure of the forced screw feeder is 10-12.5Mpa; Step 5: The raw materials after the feeder are squeezed into a high-pressure strip roller press. Under the pressure of 20-25Mpa, the extruded blocks are formed into oval long strips with a length of 100±50mm, a width of 10±5mm, and a thickness of 8±4mm; Step 6: After the oval long strips leave the roller area, they are automatically demolded and fall into a blade crusher for crushing; Step 7: The strips and fragments after being crushed by the blade crusher fall into a cage granulator. Under the action of the granulator with a filter screen of 2mm, the strips and fragments are granulated into 0-2mm particles and naturally fall into a multi-layer vibrating screen; Step 8: After being separated into 0. The qualified particle size of 5-2mm, and the materials of >2mm and <0.5mm are returned to the intermediate bin through the bucket elevator to participate in the next round of briquetting; Step 9: The finished products of qualified particle size are fluidized and stirred in the passivation chamber at 80-130℃ with 0.2%-0.3% atomized methyl silicone oil to obtain a low-carbon and low-sulfur alkaline particle covering agent. The methyl silicone oil is heated to 100-130℃ by a heater and atomized through a disc fine-pore nozzle under the action of a 0.5-0.6Mpa booster pump. Example 1
[0036] The formula design is: 50% activated carbon fly ash, 40% lime dust ash, 7% dolomite dust ash, 3% activated carbon dust ash, plus 0.25% methyl silicone oil. The production is carried out according to the steps of the above benchmark embodiment. The product test results are shown in the following table.
[0037]
[0038] After implementation, it is not easy to melt on the surface of molten steel, the spreadability is poor, the liquid slag layer is thin, the thermal insulation effect is poor, and it is sticky. Example 2
[0039] The formula design is: 65% activated carbon fly ash, 25% lime dust ash, 7% dolomite dust ash, 3% activated carbon dust ash, and 0.25% methyl silicone oil. The production is carried out according to the steps of the above benchmark embodiment. The product test results are shown in the following table.
[0040]
[0041] After implementation, the molten steel is spread evenly and the liquid slag does not stick to the bag, but the sintered layer is thin and some red is leaking. Example 3
[0042] The preferred formula is: 60% activated carbon fly ash, 30% lime dust ash, 7% dolomite dust ash, 3% activated carbon dust ash, and 0.25% methyl silicone oil, produced according to the steps of the above benchmark example. The product test results are shown in the following table.
[0043]
[0044] After implementation, the functional structure of the material layer is clear, and the melting layer, semi-sintering layer and sintering layer have achieved corresponding functional roles; when putting in molten steel, it has good thermal insulation, uniform spreadability, strong ability to adsorb inclusions, does not cause pollution such as C and S in the molten steel, and the liquid slag does not stick to the package.
[0045] The above description is only a specific embodiment of the present invention, but the structural features of the protection scope of the present invention are not limited thereto. Any changes or modifications made by any technician in the field of the present invention are all covered by the patent scope of the present invention.
Claims
1. A low-carbon, low-sulfur, low-cost alkaline granular covering agent, characterized in that: The ingredients and mass percentage are as follows: CaO: 28-42%, MgO: 3-5%, Al2O3: 12-20%, Fe2O3: 1-3%, SiO2: 25-36%, S: 0.01-0.04%, C <5%, H20: <1%, methyl silicone oil 0.2%-0.3%, and the rest are impurities that do not affect the use effect; hemisphere point 1500-1750℃, R (alkalinity) 1.0-1.5, melting rate 60-120 seconds, bulk density 0.6-0.9, particle size 0.5-2mm.
2. A low-carbon, low-sulfur, low-cost alkaline granular covering agent according to claim 1, characterized in that: The raw materials of alkaline granular covering agent are 50-70% activated carbon fly ash or slag, 20-40% lime dust ash, 6-8% dolomite dust ash, and 2-4% activated carbon dust ash.
3. A method for producing a low-carbon, low-sulfur, low-cost alkaline granular covering agent, characterized in that: The following steps are involved: Step 1: pump lime dust removal ash, dolomite dust removal ash and activated carbon dust removal ash into the raw material warehouse by tank truck for standby use; Step 2: After the activated carbon fly ash or slag is separated by a closed drum screen, the fine powder <0.1mm is sent to the raw material bin by a bucket elevator for standby use; Step 3: Various raw materials are weighed by a measuring dragon according to the ratio of 50-70% activated carbon fly ash or slag, 20-40% lime dust ash, 6-8% dolomite dust ash, and 2-4% activated carbon dust ash, and then sent to a mixer for uniform mixing, and then sent to the intermediate warehouse for standby use through a bucket elevator; Step 4: The mixed material in the intermediate bin falls through the metering feeder with a lock air valve to the forced screw feeder with a compression ratio of 5:
1. The pressure of the forced screw feeder is 10-12.5Mpa; Step 5: The raw materials after the feeder are squeezed into the high-pressure strip roller press, and under the pressure of 20-25Mpa, they are squeezed into oval strips with a length of 100±50mm, a width of 10±5mm, and a thickness of 8±4mm; Step 6: After the oval long strips leave the roller area, they are automatically demoulded and fall into the blade crusher for crushing; Step 7: The strips and fragments after being crushed by the blade crusher fall into the cage granulator. Under the action of the 2mm filter screen granulator, the strips and fragments are granulated into 0-2mm particles and naturally fall into the multi-layer vibrating screen; Step 8: The materials are separated into qualified particle sizes of 0.5-2mm through multi-layer vibrating screens, and the materials with sizes of >2mm and <0.5mm are returned to the intermediate bin through bucket elevators to participate in the next round of briquetting; Step 9: The finished product with qualified particle size is placed in a passivation chamber at 80-130℃ and fluidized and stirred with 0.2%-0.3% atomized methyl silicone oil to obtain a low-carbon and low-sulfur alkaline particle covering agent. The methyl silicone oil is heated to 100-130℃ by a heater and atomized through a disc fine-pore nozzle under the action of a 0.5-0.6Mpa booster pump.
Citation Information
Patent Citations
High-alkalinity compound particle covering agent and production method thereof
CN103740893A
Method for efficiently utilizing metallurgical solid waste
CN112301188A
Production method for improving pouring property of silicon-manganese killed silicon steel
CN113249639A
Low-cost slag ladle heat-insulation separation spray coating and production and use method thereof
CN118085617A
Treatment of fly ash contaminated with activated carbon
US20140245931A1